Il volto - Il corpo. (Venezia : Contini Galleria d'Arte)
Barbarigo, Ida ; Cadorin, Ettore ; Cadorin, Guido ; Cadorin, Vincenzo ; Casorati, Felice ; De Chirico, Giorgio ; Giacometti, Alberto ; Guarienti, Carlo ; Haas, Michel ; Kokoschka, Oskar ; Martini, Arturo ; Marussig, Piero ; Messina, Francesco ; Music, Zoran ; Nolde, Emil ; Poniatowska, Marie-Anne ; Rosso, Medardo ; Sironi, Mario
boek